An account of the Genus Turris species (Mollusca: Gastropoda: Turridae) from the East and South China Seas - Li, Baoquan; Li, Xinzheng (Zootaxa, 2007)
Five species of the genus Turris Röding, 1798 from the China seas are reported in the present paper, they are Turris grandis (Gray, 1834); T. crispa (Lamarck, 1816); T. undosa (Lamarck, 1816); T. annulata (Reeve, 1843); T. normandavidsoni Olivera, 1999. In which, T. grandis, T. undosa and T. normandavidsoni are recorded here for the first time from the China Seas. The material was collected from the South China Sea off Gongdong, Beibu Gulf, Hainan Island, Xisha Islands, Nansha Islands, and the East China Sea.